2010
DOI: 10.1177/0734016809349177
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: Gilmore, R. W. Golden Gulag: Prisons, Surplus, Crisis, and Opposition in Globalizing California Berkeley, CA: University of California Press, 2007. xxii pp., 388 pp

Abstract: Buck, and others. These ''others'' are the captive intellectuals, the many men and women of the American gulag.As a former federal prisoner that did time in four United States Penitentiaries (USP), with some of the people quoted in this book, I read Rodriguez with interest, and even a bit of foreboding. Having made it out of USP Marion and USP Leavenworth in more or less one piece, I was not eager to return. Forced Passages, despite its repetitive rhetoric, and somewhat romantic ideas about revolutionary convi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Organizing is inherently gendered, as women and men resist gendered divisions, construct meaning, and, through solidarity, assemble shared identities (Buzzanell and Liu, 2005;Salzinger, 2003). These assemblages of masculinity become enacted through an affinity toward "geekdom" (Kendall, 2002), an extension of subordinate masculinities (Connell, 2005). The geek privileges intellect and "may show little interest in physical sports and may also demonstrate awkwardness regarding sexual/romantic relationships" (Massanari, 2017: 332).…”
Section: Gendered Organizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizing is inherently gendered, as women and men resist gendered divisions, construct meaning, and, through solidarity, assemble shared identities (Buzzanell and Liu, 2005;Salzinger, 2003). These assemblages of masculinity become enacted through an affinity toward "geekdom" (Kendall, 2002), an extension of subordinate masculinities (Connell, 2005). The geek privileges intellect and "may show little interest in physical sports and may also demonstrate awkwardness regarding sexual/romantic relationships" (Massanari, 2017: 332).…”
Section: Gendered Organizingmentioning
confidence: 99%
“…In online contexts, research into gendered solidarity has shown that whereas women may use the Internet to strategize against harassment and amplify anti-racist and feminist activism (Vickery and Everbach, 2018), men have established solidarity through anti-women hate discourses (Kim, 2018). These essentialized categorizations are not fixed but represent a continuum of possible gendered-power relations (Connell, 2005). However, they nonetheless illustrate trends within men's collectivism online that orient in and order political activism.…”
Section: Gendered Organizingmentioning
confidence: 99%
“…He did not pursue this insight further, but this is the insight I would like to build on here. Surplus populations are in fact rampant in Third World slums and among marginalized groups in high-income countries, such as refugees, the homeless and the incarcerated (McIntyre, 2011;Rajaram, 2018;Willse, 2015;Wilson Gilmore, 2007). But as Gavin Smith (2011) points out, having no leverage or means through which to pursue their goals within existing institutions makes such groups singularly prone to disruptive politics.…”
mentioning
confidence: 99%